Smartphones From an Applied Research Perspective 2017
DOI: 10.5772/intechopen.69691
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry and Usage of the Supplementary Fisheye Lenses in Smartphones

Abstract: Nowadays, mobile phones are more than a device that can only satisfy the communication need between people. Since fisheye lenses integrated with mobile phones are lightweight and easy to use, they are advantageous. In addition to this advantage, it is experimented whether fisheye lens and mobile phone combination can be used in a photogrammetric way, and if so, what will be the result. Fisheye lens equipment used with mobile phones was tested in this study. For this, standard calibration of 'Olloclip 3 in one'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In general, calibration methods are based on points and lines, patterns and selfcalibration procedures. There are some studies related to calibration applied to fisheye lenses [73][74][75][76][77][78][79][80] and 360-degree cameras [51,69,70,[81][82][83], which have improved geometric results. Other studies showed comparisons between several types of cameras (perspective, fisheye, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In general, calibration methods are based on points and lines, patterns and selfcalibration procedures. There are some studies related to calibration applied to fisheye lenses [73][74][75][76][77][78][79][80] and 360-degree cameras [51,69,70,[81][82][83], which have improved geometric results. Other studies showed comparisons between several types of cameras (perspective, fisheye, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Fisheye lenses utilize specific mapping (stereographic, equidistant, equisolid angle, orthogonal), which provides the images a characteristic convex non-rectilinear appearance. 28 These specific lenses have a wide range of applications due to their ability to provide rich visual information, including the generation of augmented or virtual reality, 29 improving the performance of intelligent robot vision systems, 30 and simplifying the complexity of surveillance systems. 31 Various correction models have been proposed to rectify the distortion of fisheye lenses.…”
Section: Introductionmentioning
confidence: 99%
“…Fisheye lenses are ultra-wide angle lenses capable of taking wide panoramic or hemispheric images, however, they incorporate a significant optical distortion into the process. Fisheye lenses utilise specific mapping (stereographic, equidistant, equisolid angle, orthogonal) which lands the images a characteristic convex non-rectilinear appearance 28 . These specific lenses have a wide range of applications due to their ability to provide rich visual information, including the generation of augmented or virtual reality 29 , improving the performance of intelligent robot vision systems 30 , and simplifying the complexity of surveillance systems 31 .…”
Section: Introductionmentioning
confidence: 99%